High-infrared laser absorption rate pure copper SLM printing material and printing method
Patent Information
- Application Number
- CN202611137976.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]针对现有技术中纯铜SLM打印时红外激光吸收率低、成形质量差、工艺适配性不足等问题,本申请提供一种高红外激光吸收率纯铜SLM打印材料及打印方法,通过合理配比纳米Cr粉、纳米Nb粉与微米级球形铜粉,结合专用SLM打印工艺和时效处理工艺,在提高纯铜对红外激光吸收率的同时,保证打印零件的致密度、力学性能和导电性能,实现复杂结构纯铜零件的高质量成形
本申请提供了一种高红外激光吸收率纯铜SLM打印材料及打印方法,本申请通过在微米级球形铜粉中复配特定质量比的纳米Cr粉与纳米Nb粉,经声共振混合、真空干燥、选区激光熔化打印与时效处理,制备出高性能纯铜成形件。本申请将纯铜对1064 nm红外激光吸收率由约20%提升至90%,成形件致密度≥99.0%,同时兼顾高硬度、高抗拉强度与优异导电性能,有效解决纯铜SLM打印中激光吸收率低、成形缺陷多、性能难以协同提升的问题,可实现复杂结构纯铜零件高质量成形,适用于电子、航空航天、热管理等领域。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of metal additive manufacturing technology, and in particular to a pure copper SLM printing material and printing method with high infrared laser absorption rate. Background Technology
[0002] Pure copper possesses excellent thermal conductivity, electrical conductivity, and ductility, making it widely applicable in electronics, aerospace, and thermal management. Selective laser melting (SLM), as an advanced additive manufacturing technology, enables near-net-shape forming of complex pure copper parts without requiring extensive subsequent machining, significantly improving production efficiency and reducing material waste.
[0003] However, pure copper has extremely low absorption of infrared lasers (commonly at a wavelength of 1064nm) and extremely high thermal conductivity. This means that during SLM printing, most of the infrared laser energy is reflected, with only a small amount absorbed for powder melting, leading to defects such as unstable molten pools, incomplete fusion, porosity, and cracks. To overcome these problems, existing technologies often employ methods such as increasing laser power and improving the absorption rate of pure copper. Increasing laser power and decreasing scanning speed can cause powder splattering and excessive heat accumulation, further deteriorating print quality and increasing energy consumption and equipment wear. Methods to improve the absorption rate of pure copper mainly include alloying and powder surface coating. The introduction of alloying elements can significantly reduce electrical and thermal conductivity, while powder surface coating (such as PVD Cr or Ni plating) is complex, costly, and prone to peeling off during printing, affecting the uniformity of part composition. Furthermore, existing SLM printing technologies are not specifically designed to optimize the infrared laser absorption rate of pure copper, making it difficult to achieve a synergistic improvement in both absorption rate and forming quality.
[0004] Therefore, developing a technical solution that can effectively improve the infrared laser absorption rate of pure copper, adapt to the SLM printing process, and ensure the overall performance of parts is a technical problem that urgently needs to be solved in the field of pure copper SLM printing. Summary of the Invention
[0005] To address the problems of low infrared laser absorption rate, poor forming quality, and insufficient process adaptability in existing pure copper SLM printing technologies, this application provides a pure copper SLM printing material and method with high infrared laser absorption rate. By rationally proportioning nano-Cr powder, nano-Nb powder, and micron-sized spherical copper powder, combined with a dedicated SLM printing process and aging treatment process, the absorption rate of pure copper to infrared laser is improved while ensuring the density, mechanical properties, and electrical conductivity of the printed parts, thus achieving high-quality forming of pure copper parts with complex structures.
[0006] To achieve the above objectives, the technical solution adopted in this application is as follows: This application provides a high infrared laser absorption rate pure copper SLM printing material, which includes micron-sized spherical copper powder, nano Cr powder and nano Nb powder; Nano-Cr powder and nano-Nb powder adhere to the surface of micron-sized spherical copper powder; The amount of nano-Cr powder added is 0.4% to 4.0% of the mass of the micron-sized spherical copper powder; The amount of nano-Nb powder added is 0.3% to 3.0% of the mass of the micron-sized spherical copper powder; The mass ratio of the nano-Cr powder to the nano-Nb powder is (1.2~1.5):1.
[0007] In the technical solution of this application, the nano-Cr powder and nano-Nb powder are uniformly dispersed on the surface of micron-sized spherical copper powder to form a composite system of "micron-sized Cu powder + nano high-absorption particles". This system can effectively absorb infrared laser energy, reduce laser reflection, and improve the absorption rate of Cu powder to infrared laser. By printing the above-mentioned high infrared laser absorption pure copper SLM printing material to prepare pure copper, the absorption rate of pure copper to 1064nm infrared laser can be increased from about 20% to 90%, effectively reducing laser reflection, reducing the demand for laser power, avoiding equipment damage and powder splashing caused by high-power laser, and ensuring the stability of the molten pool while reducing defects such as incomplete fusion and porosity.
[0008] As a preferred embodiment of the high infrared laser absorptivity pure copper SLM printing material described in this application, the particle size of the micron-sized spherical copper powder is 15~53 μm.
[0009] The conventional metal powder particle size range for SLM (Selective Laser Melting) process is 15-53μm. This range can balance the powder density and laser energy absorption efficiency.
[0010] In some specific embodiments, the particle size of the micron-sized spherical copper powder is 15~45 μm.
[0011] In some embodiments of the present invention, the specific value of the particle size of the micron-sized spherical copper powder can be any one of 15μm, 45μm, and 53μm, or it can be within the range formed by any two of the above values.
[0012] In a preferred embodiment of the high infrared laser absorption rate pure copper SLM printing material described in this application, the particle size of the nano-Cr powder is 50~200 nm.
[0013] In a preferred embodiment of the high infrared laser absorption rate pure copper SLM printing material described in this application, the particle size of the nano Nb powder is 50~200 nm.
[0014] This application provides a printing method using the above-mentioned high infrared laser absorption rate pure copper SLM printing material, including the following steps: S1. Add nano-Cr powder and nano-Nb powder to micron-sized spherical copper powder to obtain a mixed powder; S2. The mixed powder is uniformly mixed by acoustic resonance to obtain the mixed powder after acoustic resonance treatment; S3. After vacuum drying, the mixed powder treated with acoustic resonance is loaded into the SLM equipment, and the powder is spread layer by layer, laser melted, cooled and solidified to complete the SLM printing and obtain the printed part. S4. Cut the printed part off the substrate and perform aging treatment to obtain the SLM molded part.
[0015] First, this application uses acoustic resonance mixing to uniformly disperse nano-Cr powder and nano-Nb powder on the surface and gaps of micron-sized Cu powder, forming a composite system of "micron-sized Cu powder + nano-high absorptive particles". This system can effectively absorb infrared laser energy, reduce laser reflection, and improve the absorption rate of Cu powder to infrared laser. Specifically, it can increase the absorption rate of pure copper to 1064nm infrared laser from about 20% to 90%, effectively reducing laser reflection, lowering the demand for laser power, avoiding equipment damage and powder splashing caused by high-power laser, while ensuring the stability of the molten pool and reducing defects such as incomplete fusion and porosity.
[0016] Furthermore, the high laser molten pool temperature and rapid solidification of SLM printing form a supersaturated Cu-Cr-Nb solid solution, resulting in the precipitation of a small amount of NbCr2 strengthening phase in the printed sample. The specific Cr / Nb mass ratio, combined with subsequent aging treatment, further precipitates a large amount of NbCr2 strengthening phase, which is dispersed in the copper matrix, significantly improving the hardness and strength of the printed parts. At the same time, it also takes into account the excellent electrical and thermal conductivity of pure copper, thus resolving the contradiction between "improving the absorption rate and ensuring the overall performance" in existing technologies.
[0017] In a preferred embodiment of the printing method described in this application, in step S2, the acceleration of acoustic resonance is 40~80 g, and the mixing time is 15~60 min.
[0018] By employing the aforementioned acoustic resonance conditions, this application can better and more uniformly attach nano-Cr and Nb powders to spherical pure copper powder, significantly improving the absorption rate of pure copper to infrared lasers. Specifically, it increases the absorption rate of pure copper to 1064nm infrared lasers from approximately 20% to 90%, effectively reducing laser reflection, lowering the demand for laser power, avoiding equipment damage and powder splashing caused by high-power lasers, while ensuring the stability of the molten pool and reducing defects such as incomplete fusion and porosity.
[0019] In a preferred embodiment of the printing method described in this application, in step S3, the vacuum drying temperature is 120°C and the drying time is 4~6 hours.
[0020] In a preferred embodiment of the printing method described in this application, the parameters for SLM printing in step S3 include: The laser wavelength is 1064 nm, the laser power is 200~400 W, the scanning speed is 500~1000 mm / s, the scanning spacing is 0.07~0.1 mm, and the single-layer powder thickness is 0.02~0.04 mm; the scanning method is "Z" shaped scanning with an interlayer rotation angle of 67°.
[0021] In a preferred embodiment of the printing method described in this application, the aging treatment in step S4 is performed under a nitrogen or argon protective atmosphere.
[0022] In a preferred embodiment of the printing method described in this application, in step S4, the aging temperature is 400~600℃ and the heat preservation time is 1~5 h.
[0023] This application provides the application of the above-mentioned high infrared laser absorptivity pure copper SLM printing material in the preparation of pure copper molded parts.
[0024] By optimizing the ratio of nano-Cr powder, nano-Nb powder and micron-sized spherical copper powder and the printing process, this invention achieves a density of ≥99.0% for printed parts, with high surface quality and dimensional accuracy. It can realize high-quality forming of complex pure copper parts and is suitable for the manufacturing of parts in various fields such as electronics, aerospace, and thermal management.
[0025] Compared with the prior art, this application has the following beneficial effects: This application provides a high infrared laser absorptivity pure copper SLM printing material and method. This application involves compounding nano-Cr powder and nano-Nb powder in a specific mass ratio into micron-sized spherical copper powder, followed by acoustic resonance mixing, vacuum drying, selective laser melting printing, and aging treatment to prepare high-performance pure copper formed parts. This application increases the absorption rate of pure copper to 1064 nm infrared laser from approximately 20% to 90%, achieving a formed part density ≥99.0%, while also maintaining high hardness, high tensile strength, and excellent electrical conductivity. It effectively solves the problems of low laser absorptivity, numerous forming defects, and difficulty in synergistic performance improvement in pure copper SLM printing. It enables high-quality forming of complex structure pure copper parts and is suitable for fields such as electronics, aerospace, and thermal management. Attached Figure Description
[0026] Figure 1 SEM images of pure copper powder and pure copper powder with added nano Cr and Nb powder; Figure 2Infrared laser absorption rate results for pure copper powder and pure copper powder with added nano-Cr and Nb powder. Detailed Implementation
[0027] To better illustrate the purpose, technical solution, and advantages of this application, the following description will be provided in conjunction with the accompanying drawings and specific embodiments.
[0028] In the following examples and comparative examples, unless otherwise specified, the experimental methods used are conventional methods, and the materials and reagents used are commercially available unless otherwise specified. Furthermore, the raw materials used in each parallel experiment are the same.
[0029] Example 1 This embodiment provides a printing method using pure copper SLM printing material with high infrared laser absorption rate, including the following steps: S1. Take 1000 g of micron-sized spherical copper powder with a particle size distribution of 15-53 μm, add 4 g of nano Cr powder with a particle size distribution of 50-200 nm and 6 g of nano Nb powder with a particle size distribution of 50-200 nm to obtain a mixed powder. S2. The mixed powder is loaded into a grinding jar and treated with an acoustic resonance instrument at an acceleration of 60 g for 15 min to obtain the acoustically treated mixed powder (i.e., spherical copper powder with high infrared laser absorption rate). S3. Place the acoustically resonant mixed powder into a vacuum drying oven and dry it at 120 ℃ for 4 h. After natural cooling, take it out and load it into an SLM device equipped with a 1064 nm wavelength laser. According to the preset process parameters (laser power 280 W, scanning speed 800 mm / s, scanning spacing 0.09 mm, single layer powder thickness 0.03 mm, "Z" shaped scanning, interlayer rotation angle 67°), perform layer-by-layer powder spreading, laser melting, cooling and solidification to complete the printing and obtain the printed part. S4. Cut the printed part off the substrate and perform aging treatment to obtain the SLM molded part.
[0030] like Figure 1 and Figure 2 As shown, by mixing with acoustic resonance, nano-Cr powder and nano-Nb powder are uniformly attached to the surface of micron-sized spherical copper powder, which significantly improves the absorption rate of micron-sized spherical copper powder to 1064 nm wavelength infrared laser from about 20% to about 90%, effectively enhancing its infrared laser printing forming capability.
[0031] Example 2 This embodiment provides a printing method using pure copper SLM printing material with high infrared laser absorption rate, including the following steps: S1. Take 1000 g of micron-sized spherical copper powder with a particle size distribution of 15-53 μm, add 12 g of nano-Cr powder with a particle size distribution of 50-200 nm and 9 g of nano-Nb powder with a particle size distribution of 50-200 nm to obtain a mixed powder. S2. The mixed powder is loaded into a grinding jar and treated with an acoustic resonance instrument at an acceleration of 60 g for 15 min to obtain the acoustically treated mixed powder (i.e., spherical copper powder with high infrared laser absorption rate). S3. Place the acoustically resonant mixed powder into a vacuum drying oven and dry it at 120 ℃ for 4 h. After natural cooling, take it out and load it into an SLM device equipped with a 1064 nm wavelength laser. According to the preset process parameters (laser power 280 W, scanning speed 800 mm / s, scanning spacing 0.09 mm, single layer powder thickness 0.03 mm, "Z" shaped scanning, interlayer rotation angle 67°), perform layer-by-layer powder spreading, laser melting, cooling and solidification to complete the printing and obtain the printed part. S4. Cut the printed part off the substrate and perform aging treatment to obtain the SLM molded part.
[0032] Example 3 This embodiment provides a printing method using pure copper SLM printing material with high infrared laser absorption rate, including the following steps: S1. Take 1000 g of micron-sized spherical copper powder with a particle size distribution of 15-53 μm, add 20 g of nano-Cr powder with a particle size distribution of 50-200 nm and 15 g of nano-Nb powder with a particle size distribution of 50-200 nm to obtain a mixed powder. S2. The mixed powder is loaded into a grinding jar and treated with an acoustic resonance instrument at an acceleration of 80 g for 60 min to obtain the acoustically treated mixed powder (i.e., spherical copper powder with high infrared laser absorption rate). S3. Place the acoustically resonant mixed powder into a vacuum drying oven and dry it at 120 ℃ for 4 h. After natural cooling, take it out and load it into an SLM device equipped with a 1064 nm wavelength laser. According to the preset process parameters (laser power 280 W, scanning speed 800 mm / s, scanning spacing 0.09 mm, single layer powder thickness 0.03 mm, "Z" shaped scanning, interlayer rotation angle 67°), perform layer-by-layer powder spreading, laser melting, cooling and solidification to complete the printing and obtain the printed part. S4. Cut the printed part off the substrate and perform aging treatment to obtain the SLM molded part.
[0033] Example 4 This embodiment provides a printing method using pure copper SLM printing material with high infrared laser absorption rate, including the following steps: S1. Take 1000 g of micron-sized spherical copper powder with a particle size distribution of 15-53 μm, add 40 g of nano-Cr powder with a particle size distribution of 50-200 nm and 30 g of nano-Nb powder with a particle size distribution of 50-200 nm to obtain a mixed powder. S2. The mixed powder is loaded into a grinding jar and treated with an acoustic resonance instrument at an acceleration of 80 g for 40 min to obtain the acoustically treated mixed powder (i.e., spherical copper powder with high infrared laser absorption rate). S3. Place the acoustically resonant mixed powder into a vacuum drying oven and dry it at 120 ℃ for 4 h. After natural cooling, take it out and load it into an SLM device equipped with a 1064 nm wavelength laser. According to the preset process parameters (laser power 280 W, scanning speed 800 mm / s, scanning spacing 0.09 mm, single layer powder thickness 0.03 mm, "Z" shaped scanning, interlayer rotation angle 67°), perform layer-by-layer powder spreading, laser melting, cooling and solidification to complete the printing and obtain the printed part. S4. Cut the printed part off the substrate and perform aging treatment to obtain the SLM molded part.
[0034] Comparative Example 1 Compared with Example 1, the difference in Comparative Example 1 is that the printing method does not add nano Cr powder and nano Nb powder, while the remaining steps are the same as in Example 1.
[0035] Comparative Example 2 Compared with Example 1, the difference in Comparative Example 2 is that the printing method does not add nano Cr powder, while the remaining steps are the same as in Example 1.
[0036] Comparative Example 3 Compared with Example 1, the difference in Comparative Example 3 is that the printing method does not add nano Nb powder, while the remaining steps are the same as in Example 1.
[0037] Comparative Example 4 Compared with Example 1, the difference in Comparative Example 4 is that the added nano Cr powder and Nb powder are 10 g and 10 g respectively, while the rest of the steps are the same as in Example 1.
[0038] Comparative Example 5 Compared with Example 1, the difference in Comparative Example 5 is that the added nano Cr powder and Nb powder are 10 g and 5 g, respectively, while the rest of the steps are the same as in Example 1.
[0039] Density measurements were performed on the SLM molded parts prepared in Examples 1-5 and Comparative Examples 1-7 according to ASTM B962-23; hardness tests were performed on the SLM molded parts prepared in Examples 1-5 and Comparative Examples 1-7 according to GB / T4340.1-2009; volume resistivity tests were performed on the SLM molded parts prepared in Examples 1-5 and Comparative Examples 1-7 according to GB / T351-2019, and then converted to conductivity according to the International Standard for Annealed Copper (%IACS); tensile strength tests were performed on the SLM molded parts prepared in Examples 1-5 and Comparative Examples 1-7 according to GB / T 228.1-2021.
[0040] The test results are shown in Table 1.
[0041] Table 1 As shown in Table 1, the density, hardness, conductivity, and tensile strength of the samples in Examples 1-4 are all higher than those in Comparative Examples 1-5. This is because the nano-Cr powder and nano-Nb powder synergistically enhance the infrared laser absorption rate, allowing the molten pool to fully melt and reducing defects to improve density. In addition, the addition of a specific proportion of nano-Cr powder or Nb powder mainly forms the NbCr2 strengthening phase after printing and heat treatment, resulting in a more significant strengthening effect. At the same time, it reduces the damage to the copper lattice caused by the solid solution of a single element. Compared with adding nano-Cr (Nb) powder alone or with an excessively large (or small) proportion of nano-Cr / Nb powder, the specific proportion of addition balances hardness, tensile strength, and conductivity.
[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.
Claims
1. A pure copper SLM printing material with high infrared laser absorption rate, characterized in that, The high infrared laser absorption rate pure copper SLM printing material includes micron-sized spherical copper powder, nano Cr powder, and nano Nb powder. Nano-Cr powder and nano-Nb powder adhere to the surface of micron-sized spherical copper powder; The amount of nano-Cr powder added is 0.4% to 4.0% of the mass of the micron-sized spherical copper powder; The amount of nano-Nb powder added is 0.3% to 3.0% of the mass of the micron-sized spherical copper powder; The mass ratio of the nano-Cr powder to the nano-Nb powder is (1.2~1.5):
1.
2. The high infrared laser absorption rate pure copper SLM printing material as described in claim 1, characterized in that, The particle size of the micron-sized spherical copper powder is 15~53 μm.
3. The high infrared laser absorption rate pure copper SLM printing material as described in claim 1, characterized in that, The particle size of the nano-Cr powder is 50~200 nm.
4. The high infrared laser absorption rate pure copper SLM printing material as described in claim 1, characterized in that, The particle size of the nano-Nb powder is 50~200 nm.
5. A printing method using a high infrared laser absorptivity pure copper SLM printing material as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Add nano-Cr powder and nano-Nb powder to micron-sized spherical copper powder to obtain a mixed powder; S2. The mixed powder is uniformly mixed by acoustic resonance to obtain the mixed powder after acoustic resonance treatment; S3. After vacuum drying, the mixed powder treated with acoustic resonance is loaded into the SLM equipment, and the powder is spread layer by layer, laser melted, cooled and solidified to complete the SLM printing and obtain the printed part. S4. Cut the printed part off the substrate and perform aging treatment to obtain the SLM molded part.
6. The printing method as described in claim 5, characterized in that, In step S2, the acceleration of acoustic resonance is 40~80g, and the mixing time is 15~60 min.
7. The printing method as described in claim 5, characterized in that, In step S3, the vacuum drying temperature is 120℃ and the drying time is 4~6 h.
8. The printing method as described in claim 5, characterized in that, In step S3, the parameters for SLM printing include: The laser wavelength is 1064 nm, the laser power is 200~400 W, the scanning speed is 500~1000 mm / s, the scanning spacing is 0.07~0.1 mm, and the single-layer powder thickness is 0.02~0.04 mm; the scanning method is "Z" shaped scanning, and the interlayer rotation angle is 67°.
9. The printing method as described in claim 5, characterized in that, In step S4, the aging treatment is carried out under a nitrogen or argon protective atmosphere. And / or, the aging temperature is 400~600℃, and the holding time is 1~5 h.
10. The application of the high infrared laser absorptivity pure copper SLM printing material as described in any one of claims 1 to 4 in the preparation of pure copper molded parts.